Identification of a Non-Retinoid Opsin Ligand Through Pharmacophore-Guided Virtual Screening—A Novel Potential Rhodopsin-Stabilizing Compound - Miriana Di Stefano; Maria Ghilardi; Clarissa Poles; Lisa Piazza; Gian Carlo Demontis; Giulio Poli; Tiziano Tuccinardi; Marco Macchia (Molecules)
Rhodopsin, a G-protein-coupled receptor (GPCR) comprising the protein opsin covalently linked to the chromophore 11-cis retinal, is pivotal in visual phototransduction. Mutations in the gene encoding rhodopsin (RHO) can cause opsin misfolding or reduce its stability, resulting in retinal degenerative disorders such as retinitis pigmentosa (RP). Current therapeutic strategies employing retinoid-based chaperones partially rescue the folding and trafficking of mutant rhodopsin, but are limited by inherent toxicity and instability due to photoinduced isomerization. In the present work, a pharmacophore-based virtual screening protocol combined with molecular docking and molecular dynamics simulations was employed, leading to the identification of a novel non-retinoid opsin ligand that can potentially act as a pharmacological chaperone. Biological validation confirmed that the compound VS1 binds opsin effectively, representing a valuable starting point for structure-based optimization studies aimed at identifying new opsin stabilizers.